Performance-Based Building: Key Concepts, Opportunities, Barriers and Paradigm of Proposed Solution - arslan, serkan (Advances in Social Sciences Research Journal, 2018)
ABSTRACT It is a reality expressed also in the literature that it has become inevitable now for the construction industry, which adopted specific patterns as to the production process until recently arising from various impossibilities as well as for practical reasons within and without the sector, to take into consideration the developing and changing conditions and approach reconstruction works in this sense including the cited changes. In line with this approach, starting point of this study comprises determination of key concepts as competition by design, competitive advantage, interoperability, integration, building information modeling, innovativeness, information technology and performance and the entire process must be rethought with an integrated point of view within the context of "performance-based building". It has been studied on models for measuring performance at various levels in the construction sector for a long time. The most fundamental shortcoming in this area is that much as there is a basic perception for considering these studies as a whole in the process from the preliminary decision stage to the end of the construction stage in construction projects, the main axles belonging to "an approach of making a structure showing system behavior" have not been set forth with an integrated approach at a sufficient level in line with this perception. This study aims to discuss the need for change of the "performance-based building" concept in building production in present conditions – even if not for the whole sector- and using it as a tool for putting into practice in the required and eligible projects by trying to basically discuss the elements deemed primary together as far as possible and by getting into details only for necessary points , due to the vast context thereof, and put forward and base on the limited number of concepts listed hereinabove while doing so. As a result of this process, it will be tried to determine the infrastructure requirements, possibilities and existing barriers needed to put the concept to practice and, in the light of these, to define required structures needed for organization structure, information technology and measurement/calculation/evaluation systems at conceptual level.